Epidemiological aspects of patients hospitalized for Tuberculosis in the state of Sergipe between 2019 and 2023 (Research, Society and Development, 2025)
This study aims to analyze the epidemiological profile of hospitalizations for tuberculosis (TB) in the state of Sergipe between 2019 and 2023. This is a descriptive, observational, qualitative and quantitative study conducted through the analysis of data available on the portal of the Department of Information and Informatics of the Unified Health System (DATASUS) of the Ministry of Health (MS). The following variables were observed: incidence of hospitalizations for tuberculosis, hospital expenses, deaths, sex, and age group. The study shows that there were 233 hospitalizations in the state of Sergipe due to pulmonary tuberculosis during the analyzed period. The concentration of TB cases was in urban areas, especially in Aracaju, with the most prevalent age group and sex being adult men between 20 and 59 years old. It was observed that 2020 was the year with the highest number of hospitalizations, with an annual average of 44.6 cases during the analyzed period. The total number of deaths was 30, with 2019 leading this ranking. Total hospital expenses were R$145,000, making 2019 the most costly year for the public coffers. It is essential that tuberculosis control efforts in Sergipe align with the guidelines of the National Plan to End Tuberculosis as a Public Health Problem, focusing on continuous monitoring, health education, early diagnosis, and strengthening healthcare networks to reduce new cases and deaths.